2021
DOI: 10.1093/ptj/pzab162
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Training to Decrease Ectopic Intermuscular Adipose Tissue in Individuals With Chronic Diseases: A Systematic Review and Meta-Analysis

Abstract: Objective The purpose of this study was to evaluate the effect of exercise training on ectopic fat within skeletal muscle (intermuscular adipose tissue [IMAT]) in adult populations with chronic diseases. Methods A literature search was conducted in relevant databases to identify randomized controlled trials (RCTs) from inception. Selected studies examined the effect of aerobic training (AET), resistance training (RT), or comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 66 publications
0
25
0
Order By: Relevance
“…The relationship between FAP adipogenesis, a primary inducer of IMAT [5][6][7] , and chronic physical exercise, a known suppressor of IMAT 11 , has been poorly understood. To address this critical shortcoming, this study identified genes associated with FAP adipogenesis and performed GSEA to demonstrate that chronic resistance exercise and immobilization differentially regulated FAP adipogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between FAP adipogenesis, a primary inducer of IMAT [5][6][7] , and chronic physical exercise, a known suppressor of IMAT 11 , has been poorly understood. To address this critical shortcoming, this study identified genes associated with FAP adipogenesis and performed GSEA to demonstrate that chronic resistance exercise and immobilization differentially regulated FAP adipogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…While accumulated evidence has shown that IMAT is affected by muscle contractile activity (i.e., IMAT is reduced by resistance exercise but increased by immobilization) [11][12][13] , the underlying molecular mechanism is unclear. To address this gap, we first summarized the transcriptomic response of elderly skeletal muscle to resistance exercise versus immobilization.…”
Section: Resistance Exercise and Immobilization Differentially Regula...mentioning
confidence: 99%
“…However, as a rehabilitation professional, the question that needs to be addressed is which type of exercise (general vs. LuM isolated exercises) is more likely to reduce LuM MFI. With regard to general exercises (aerobic, resistance or combined training), one systematic review and meta‐analysis was conducted in adults with different chronic diseases, affecting different muscles (Tuñón‐Suárez et al, 2021). The authors concluded that aerobic and combined training of moderate intensity reduce MFI and that this effect is associated with exercise‐induced body weight and fat mass losses.…”
Section: Discussionmentioning
confidence: 99%
“…This might be due to local injury of the TLF (Bishop et al, 2016), triggering inflammation in the fasciae and its remodelling (Zugel et al, 2018), as this is the case for MFI (Hodges et al, 2021). If so, aerobic exercises may help, as this is the case for MFI (Tuñón-Suárez et al, 2021). From a mechanical perspective, having fatty infiltration of the TLF may alter its elastic modulus, or ability to extend under a certain load, and thus have an important role in local load allocation (Newell & Driscoll, 2021a;Newell & Driscoll, 2021b) (Delitto et al, 1995) and more specifically, with patients thought to have movement coordination impairment, segmental hypermobility or clinical lumbar instability (Cook et al, 2006;Delitto et al, 2012;Rabin et al, 2013).…”
Section: Thoracolumbar Fascia Thicknessmentioning
confidence: 99%
“…At the same time, there are many unresolved issues in the conduct of physical therapy [2]. In particular, there is no single protocol for assessing the functional status of people infected by human immunodeficiency virus and dosing exercise [3].…”
Section: Introductionmentioning
confidence: 99%